The Handbook of social psychology - The_Handbook ... (Amerind Publishing, 1969)
Oen, Vol. I=C. 1; Vol. III= C.1/oen, Vol. II=c.1; Vol. IV= c.1/tr, vol. V=c.1/oen, Vol.1-4=c.2/stoc6, jl.1-4=c.1-2; jl.5=c.1